The good, the bad, and the yellow - King, Trey. (Little, Brown and Company, 2017)
An introduction to the characters of "Despicable Me 3," reveals why the Minions go on strike, how Dru and Gru are related, and what Balthazar Bratt's target is.
At head of title: Illumination presents Despicable Me 3.
Keywords: Despicable me 3 (Motion picture) -- Juvenile literature